Accelerating Sustainable Performance of Balinese Woven MSMEs Through Digital Innovation and Green Entrepreneurship - Antara, Made Ermawan Yoga (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to investigate the influence of digital innovation and green entrepreneurship on MSMEs performance. Methodology: The study took place in the eastern part of Bali with respondents from ikat endek weaving MSMEs. Quantitative methods with a survey approach were used in data collection. SEM-PLS analysis was used to test the relationship between research variables. Results: Digital innovation and green entrepreneurial orientation had a significant effect on performance. On the other hand, entrepreneurial orientation was positively correlated with creativity, but not so with digital innovation. Findings: Ikat endek weaving MSMEs cannot only focus on digital technology, but must also strengthen managerial aspects and marketing strategies so that creativity can drive optimal performance. Green entrepreneurial values need to be continuously improved as a long-term strategy to strengthen competitiveness and achieve business sustainability. Novelty: The integrated model of digital innovation and green entrepreneurship targeting MSME performance is a novelty of this research. Originality: This study contributes to the growing literature on the relationship between digital innovation, green entrepreneurship, creativity, and performance in the context of local culture-based MSMEs. Conclusion: This study shows that digital innovation has no significant effect on creativity, but does significantly impact employee performance in Balinese endek ikat weaving MSMEs. Type of Paper: Research article.